The Role of Agroforestry Systems for Enhancing Biodiversity and Provision of Ecosystem Services in Agricultural Landscapes in Southeast Asia - Rahman, S.A.; Samsudin, Y.B.; Bhatta, K.P.; Aryal, A.; Hayati, D.; Cahya, M.; Trihadmojo, B.; Husain, I.; Andini, S.; Narulita, S.; Rahman, M.A.; Lu, X.; et al. (Springer, 2023)
Biodiversity has a pivotal role to play in providing ecosystem goods and services, which is under threat due to various anthropogenic activities. This chapter is based on literature review to assess the role of agroforestry to enhance biodiversity and ecosystem services in Southeast Asian agricultural landscapes. The reviewed literature was analysed through narrative qualitative and narrative comparative methods. The review provides substantial evidence that agroforestry systems can conserve species diversity and enhance ecosystem services. Farmers’ cultivating diverse species in agroforestry is the key to enhance biodiversity on farmlands that can also lessen the pressure on local forest. Careful agroforestry plantation design will not only increase the multiple ecosystem functions but can also create corridors and buffer zones to support natural habitats, to reduce human and wildlife conflict. The case of human conflicts with Asian elephants is an obvious example. From ethical ground to support elephant’s right to survive, further research on agroforestry modelling is required to benefits both humans and elephants.